The effects of oral and vaporized cannabis alone, and in combination with alcohol, on driving performance using the STISIM driving simulator: A two-part, double-blind, double-dummy, placebo-controlled, randomized crossover clinical laboratory protocol - Zamarripa, C. Austin; Novak, Matthew D.; Weerts, Elise M.; Vandrey, Ryan; Spindle, Tory R. (Frontiers in Pharmacology, 2022)
The legalization of cannabis for medicinal and non-medicinal purposes, and the corresponding increase in diversity of cannabis products, has resulted an urgent need for cannabis regulatory science. Among the most pressing needs is research related to impairment due to cannabis exposure, especially on driving performance. The present project was designed to evaluate the impact of oral and vaporized cannabis, when administered alone or in combination with alcohol, on simulated driving performance (STISIM driving simulator), cognitive/psychomotor ability, and field sobriety performance. Healthy adults will complete two, double-blind, double-dummy, placebo-controlled, randomized crossover clinical laboratory studies, one with oral cannabis dosing (16 men/16 women) and the second with vaporized cannabis dosing (16 men/16 women). In each study, participants will complete seven experimental test sessions during which acute doses of placebo or high 9-THC cannabis containing 0, 10, or 25mg 9-THC will be administered both alone and in combination with placebo or alcohol-containing beverages (target breath alcohol concentrations, BAC, of 0.0% or 0.05%). An additional positive control session (i.e., alcohol at target BAC of 0.08% with placebo cannabis) will also be completed. Simulated driving performance tests (available for download; see Methods), field sobriety assessments, subjective drug effect questionnaires, a mobile device impairment test (DRUID app), and collection of whole blood specimens will be completed repeatedly during each session. Linear mixed models will be used to test for differences across experimental conditions and a priori planned comparisons will be used to determine differences between active dose conditions and placebo as well as differences between conditions of interest (e.g., each active cannabis dose vs. the same cannabis dose with alcohol). This research is designed to extend prior studies of cannabis and alcohol on driving performance by using oral and vaporized routes of cannabis administration. By increasing understanding of impairment associated with co-use of alcohol and these novel forms of cannabis, this research could inform impairment detection standards for cannabis and alcohol and have important implications for law enforcement (e.g., informing how to test for cannabis impairment), public policy decisions regarding accessibility of these substances, and education of the general population who may use cannabis and/or alcohol.